2022
DOI: 10.4103/1673-5374.320974
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNA in retinal ganglion cell health and disease

Abstract: miRNA are short non-coding RNA responsible for the knockdown of proteins through their targeting and silencing of complimentary mRNA sequences. The miRNA landscape of a cell thus affects the levels of its proteins and has significant consequences to its health. Deviations in this miRNA landscape have been implicated in a variety of neurodegenerative diseases and have also garnered interest as targets for treatment. Retinal ganglion cells are the sole projection neuron of the retina with their axons making up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…Overall, stem cell-derived EVs promote cell proliferation, resist apoptosis, suppress inflammatory responses, repair retinal structures, and restore visual capacity in various retinal disease models. Most studies on retinal damage repair by stem cell-derived EVs have shown that miRNAs mainly mediate the molecular mechanisms underlying the actions of stem cell-derived EVs [ 55 , 56 ]. Ben Mead et al knocked down Argonaute-2, a key miRNA effector molecule, in bone marrow mesenchymal stem cells (BMSCs) and implanted BMSC-derived EVs (BMSC-EVs) into the eyes of optic nerve crush model mice [ 57 ].…”
Section: Main Textmentioning
confidence: 99%
“…Overall, stem cell-derived EVs promote cell proliferation, resist apoptosis, suppress inflammatory responses, repair retinal structures, and restore visual capacity in various retinal disease models. Most studies on retinal damage repair by stem cell-derived EVs have shown that miRNAs mainly mediate the molecular mechanisms underlying the actions of stem cell-derived EVs [ 55 , 56 ]. Ben Mead et al knocked down Argonaute-2, a key miRNA effector molecule, in bone marrow mesenchymal stem cells (BMSCs) and implanted BMSC-derived EVs (BMSC-EVs) into the eyes of optic nerve crush model mice [ 57 ].…”
Section: Main Textmentioning
confidence: 99%
“…Optic neuropathy is a condition characterized by damage to the optic nerve, composed of axons of neural cells known as RGCs ( 178 ). Optic neuropathy is commonly associated with optic neuritis and ischemic optic neuropathy, which may lead to permanent visual loss ( 179 ).…”
Section: Neuropathy and Tumorsmentioning
confidence: 99%
“…The miRNAs are essential factors that regulate the regeneration and protection of RGCs and the induction of inflammation ( 178 ). Furthermore, secretomes derived from stem cells and amnion cells showed promising effects on optic neuropathies ( 188 190 ).…”
Section: Neuropathy and Tumorsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Dysregulation of miRNAs has been implicated in multiple diseases, including but not limited to lung, cervical, and breast cancers. 6,9,10 Owing to their compact size (19-24 nucleotides) and comparatively more straightforward biological processes than proteins and DNA, 11,12 miRNAs are considered valuable biomarkers for disease diagnosis and therapy targets. [13][14][15][16][17] However, traditional miRNA analysis methods, such as those involving uorescent hybridization probes (including electrochemical [18][19][20] and quantitative real-time polymerase chain reaction (qPCR) 21 approaches) and MS2 RNA binding protein-uorescent protein systems, [22][23][24][25][26][27] have limitations in terms of probe degradation, delivery challenges, complex kinetics, [21][22][23][24] and inability to visualize multiple miRNA targets in a single cell, hindering their effectiveness.…”
Section: Introductionmentioning
confidence: 99%